2012
DOI: 10.1007/s00586-012-2553-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus conservative care for neck pain: a systematic review

Abstract: Objective General practitioners refer patients with continued neck pain that do not respond well to conservative care frequently to secondary care for further assessment. Are surgical interventions to the cervical spine effective when compared to conservative care for patients with neck pain? Design Systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
(52 reference statements)
1
31
0
1
Order By: Relevance
“…As surgery is associated with a small but definite risk [6], conservative management is a suggested first treatment choice in the absence of serious neurological deficits [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…As surgery is associated with a small but definite risk [6], conservative management is a suggested first treatment choice in the absence of serious neurological deficits [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…No superior conservative treatment (42), or surgical treatment method (18) has been found, and there is a lack of evidence regarding the appropriate postoperative rehabilitation (43). Also, the current evidence does not show significant benefit of surgical treatment compared to conservative treatment (44). The clinical decision making process regarding when and which individuals to include for surgery for cervical degenerative disc disease cannot be made on evidence at this time.…”
Section: Management Of Cervical Degenerative Disc Diseasementioning
confidence: 66%
“…Despite these early differences, no significant differences in pain, disability or physical function between the surgically and conservatively treated groups were present at 15-month (57) or 2-year follow-ups (16,55). A number of review studies have found no clear benefits of surgical treatment compared to conservative treatment of neck pain with or without radiculopathy (44,58).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The paper by van Middelkoop et al [20] published in January is a high-quality Cochrane systematic review investigating clinical trials on surgical treatment compared with conservative care in neck pain patients. A former Cochrane review based only on randomized trials had concluded that in the absence of pertinent data no conclusion could be provided on this subject.…”
Section: Surgery Versus Conservative Care For Neck Painmentioning
confidence: 99%